Gulliver's travels - Swift, Jonathan (Maqbool books Karachi, 2012)
Gulliver's Travels is a satirical novel by Jonathan Swift, published in 1726. The story follows Lemuel Gulliver, a ship's surgeon, who embarks on a series of extraordinary voyages to distant lands. He encounters bizarre societies, including the tiny Lilliputians, the giant Brobdingnagians, the intellectually obsessed Laputans, and the noble but inhuman Houyhnhnms. Through Gulliver's adventures, Swift critiques human nature, politics, science, and the social structures of the time. The novel blends fantasy with sharp social commentary, questioning the values and practices of European civilization.